Non-mutagenic Ru( ii )–phosphine-based complexes induce mitochondria-mediated apoptosis in breast cancer cells: from 2D to 3D investigations - Palmeira-Mello, Marcos V.; Teixeira, Tamara; Costa, Analu R.; Machado, Aline Maria; De Grandis, Rone A. [UNESP]; de Oliveira, Leticia P.; Moraes, Carlos A. F.; de Araujo-Neto, João H.; Deflon, Victor M.; Andricopulo, Adriano D.; Ellena, Javier; Selistre-de-Araújo, Heloisa S.; et al. (Royal Society of Chemistry (RSC), 2025)
Non-mutagenic ruthenium( ii )–phosphine complexes stop tumor growth in MCF-7 3D spheroids and induce apoptosis via mitochondrial damage. Three ruthenium( ii )–phosphine-based complexes with the general formula [Ru(N–S)(dppm) 2 ]PF 6 (Ru1–Ru3) were prepared and studied as anticancer agents [N–S represents 2-mercapto-2-thiazoline (Hmtz), mercapto-1-methylimidazole (Hmmi) and 4,6-diamino-2-mercapto-pyrimidine (Hdmp), and dppm represents 1,1′-bis(diphenylphosphino)methane]. The distribution coefficients of these compounds were assessed, and log P values indicated their preference for the organic phase. After confirming their stability in solution, their in vitro cytotoxicity was investigated on different breast cell lines. Our findings revealed that Ru2 was 50-fold more cytotoxic and almost 2-fold more selective than the cisplatin control, considering MCF-7 cells. Also, Ru2 induced morphological changes and inhibited colony formation in this cell line. Considering the advantages of 3D cell culture models for screening new anticancer drug candidates, the effect of Ru2, which was found to be the best candidate compound, was investigated on multicellular tumor spheroids. A live/dead assay revealed a dead cell population in both 2D and 3D MCF-7 cell models upon treatment at the IC 50 concentration. The ruthenium–phosphine complex was able to affect cell cycle distribution and mitochondrial membrane potential, inducing apoptotic cell death. Ames and micronucleus tests indicated the absence of mutagenicity for Ru2. To the best of our knowledge, this work demonstrated for the first time the effects of a ruthenium–phosphine complex on MCF-7 breast cancer cells using 2D and 3D cell-based models, highlighting its potential as a promising anticancer agent.